The Impact of Multinational Companies In Fmcg Sector: Exploring the Current and Future Trends in the FMCG Sector (Journal of Advances and Scholarly Researches in Allied Education, 2015)
With the increase in literacy level, rising per capitaincome, rapid urbanization, and Indian economy is moving ahead with leaps andbounds at both national and international level. An upsurge in no ofMultinational Corporations (MNC’s) has been witnessed that had led to the greatproliferation of wide variety of products and brands available for customers.Fast moving consumer goods (FMCG) are recognized by almost everyone because ofits stronger presence in almost every retail outlet both organized andunorganized, advertisements on television, print media, and so on. Big giantsdealing in fast moving consumer goods are growing and posting stellar top linegrowth, coming up with innovative plans so as to meet and satisfy the needs ofthe customers. This paper focuses on the trends of FMCG, the key potentialdrivers that will accelerate the existing trend and future growth. The paper willalso discuss the future implications of FMCG.